2020
DOI: 10.3390/jcm9082425
|View full text |Cite
|
Sign up to set email alerts
|

Evaluate the Differences in CT Features and Serum IgG4 Levels between Lymphoma and Immunoglobulin G4-Related Disease of the Orbit

Abstract: Background: Benign immunoglobulin G4 (IgG4)-related orbital disease (IgG4-ROD)—characterized as tumors mimicking malignant orbital lymphoma (OL)—responds well to steroids, instead of chemotherapy, radiotherapy and/or surgery of OL. The objective of this study was to report the differences in computed tomography (CT) features and- serum IgG4 levels of IgG4-ROD and OL. Methods: This study retrieved records for patients with OL and IgG4-ROD from a pathology database during an eight-year-and-five-month period. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Klingenstein et al 22 reported that there is no radiological difference between these 2 conditions, and it is impossible to differentiate the 2 entities clinically. Yuan et al 38 reported that orbital lymphoma was more commonly unilateral and showed molding features radiologically when compared with Ig-G4-ROD. Yoo et al 39 reported that T2 isointensity on MRI and hyperattenuation on precontrast CT images were observed in some IgG4-mucosa-associated lymphoid tissue lymphoma cases.…”
Section: Discussionmentioning
confidence: 99%
“…Klingenstein et al 22 reported that there is no radiological difference between these 2 conditions, and it is impossible to differentiate the 2 entities clinically. Yuan et al 38 reported that orbital lymphoma was more commonly unilateral and showed molding features radiologically when compared with Ig-G4-ROD. Yoo et al 39 reported that T2 isointensity on MRI and hyperattenuation on precontrast CT images were observed in some IgG4-mucosa-associated lymphoid tissue lymphoma cases.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with orbital lymphoma, IgG4-ROD presents with regular rather than irregular lesion borders, presents more frequently with lacrimal gland involvement, and with bilateral and multiple lesions according to a CT study from Taiwan 41 . However, another study in German patients did not find any CT imaging differences between both diseases 42 …”
Section: Head and Neck Limited Phenotypementioning
confidence: 99%
“…This Special Issue on auto-inflammation also contains relevant contribution that have been rarely addressed in such detail elsewhere. To highlight just a few points, one can read about the current options of imaging in auto-inflammation [ 5 ] with special attention to IgG4 related diseases [ 6 ] or about the issue of dysphagia in myositis [ 7 ]. Furthermore, this Special Issue also contains valuable original work, such as studies providing basic data on a novel variant of TNF receptor-associated periodic syndrome [ 8 ], drug hepatotoxicity in the treatment of gouty arthritis [ 9 ], the impact of certain anti-rheumatic drugs on DNA repair [ 10 ], genetic background in association with response to anti-rheumatic drugs [ 11 ], and the impact of IL1-inhibition on the cytokine milieu in adult-onset Still’s disease [ 12 ].…”
mentioning
confidence: 99%